2019
DOI: 10.1111/jgh.14941
|View full text |Cite
|
Sign up to set email alerts
|

Automatic detection of blood content in capsule endoscopy images based on a deep convolutional neural network

Abstract: Background and AimDetecting blood content in the gastrointestinal tract is one of the crucial applications of capsule endoscopy (CE). The suspected blood indicator (SBI) is a conventional tool used to automatically tag images depicting possible bleeding in the reading system. We aim to develop a deep learning‐based system to detect blood content in images and compare its performance with that of the SBI.MethodsWe trained a deep convolutional neural network (CNN) system, using 27 847 CE images (6503 images depi… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
3
1
1

Citation Types

1
66
0
1

Year Published

2020
2020
2023
2023

Publication Types

Select...
8
1

Relationship

0
9

Authors

Journals

citations
Cited by 89 publications
(68 citation statements)
references
References 10 publications
1
66
0
1
Order By: Relevance
“…It outperformed earlier classifiers with sensitivity, specificity, and accuracy more than 98% and displayed a segmentation of bleeding zones within abnormal frames. Furthermore, Aoki et al 13 developed a less supervised neural network-based algorithm based on PillCam SBCE still images. This AI solution was trained on 6503 images with blood and 21 334 without blood and then assessed on 208 images with blood and 10 000 without blood.…”
Section: Detection Of Lesions and Abnormalitiesmentioning
confidence: 99%
“…It outperformed earlier classifiers with sensitivity, specificity, and accuracy more than 98% and displayed a segmentation of bleeding zones within abnormal frames. Furthermore, Aoki et al 13 developed a less supervised neural network-based algorithm based on PillCam SBCE still images. This AI solution was trained on 6503 images with blood and 21 334 without blood and then assessed on 208 images with blood and 10 000 without blood.…”
Section: Detection Of Lesions and Abnormalitiesmentioning
confidence: 99%
“…In 2019, Aoki et al reported a CNN system for detecting blood content, and compared its performance with that of the suspected blood indicator (SBI), which automatically tags images with suspicious hemorrhages in the reading system. 30 The dataset consisted of 27,847 total CE images, including a training dataset of 6,503 images depicting blood content from 29 patients and a validation dataset of 10,208 images with 208 images depicting blood content. This CNN system outperformed the conventional SBI in terms of sensitivity (96.6% vs. 76.9%), specificity (99.9% vs. 99.8%), and accuracy (99.9% vs. 99.3%).…”
Section: Application Of Artificial Intelligence In Capsule Endoscopymentioning
confidence: 99%
“…The AUROC for detecting angioectasia was 0.998, and the sensitivity and specificity were 98.8% and 98.4%, respectively. In 2019, Aoki et al reported a CNN system for detecting blood content, and compared its performance with that of the suspected blood indicator (SBI), which automatically tags images with suspicious hemorrhages in the reading system [ 30 ]. The dataset consisted of 27,847 total CE images, including a training dataset of 6,503 images depicting blood content from 29 patients and a validation dataset of 10,208 images with 208 images depicting blood content.…”
Section: Artificial Intelligence In Capsule Endoscopymentioning
confidence: 99%
“…When CNN-based interpretations were used for the detection of angioectasia, the most common SB vascular lesion, it demonstrated excellent sensitivity and specificity close to 100% [ 45 , 46 ]. In addition, CNN-based interpretations showed an accuracy of 90.8% in the diagnosis of SB erosions and ulcers [ 47 ] and showed a higher diagnostic accuracy in blood contents (sensitivity, 96.63%; specificity, 99.96%) compared to conventional suspected blood indicators [ 48 ]. In a large-scale study in China, a new CNN interpretation model based on 113,426,569 images was developed, which showed a higher sensitivity (77.9%–99.9%) and lesion detection rate (54.6%–70.9%) compared to conventional CE interpretations for detecting various SB lesions, such as inflammation, ulcers, and polyps.…”
Section: Artificial Intelligence-based Interpretation Programmentioning
confidence: 99%